AN ANALYSIS OF USING MINIMAL PAIRS IN PRONOUNCING CONSONANTS AND VOWELS - Debby Citra Dewi; Diah Astriyanti (XXXX-XXXX, 2021)
This research aimed to describe pronunciation error and correct pronunciation in English consonants and vowels by the participants on Phonology subject.  The data were from the fourth semester students of English education study program. Furthermore, all of the students that participated there were 12 students. This research applied a descriptive study with qualitative approach. The data of this research was collected by test and documentation. To conduct the test, the researcher chose minimal pair words which are focused on thirteen English consonant sounds: /ð/, /t/, /d/, /s/, /z/, /f/, /v/, /k/, /g/, /ʔ/, /tʃ/, /dʒ/, and /h/.  Then, nine vowel sounds, there were : /iː/, /ɪ/, /e/, /o/, /ɔː/, /eɪ/, /ɑː/, /әʊ/, and /æ/. Additionally, the documents consisted of students’ voice such as audio recorded. The research finding were analyzed how many of them who made error in pronouncing the minimal pairs words. There were 3 steps in analyzing data, such as data reduction, data display, and conclusion/verification. For the result of this research, it shows that the dominant pronunciation errors made by the fourth students semester was in English consonant sounds /s/ and /z/. The students who made pronunciation error was 91,7%. Whereas, the dominant errors pronunciation of minimal pair words by the participants in vowel sounds were /æ/ and /eɪ/. The students made pronunciation error was 91,7%.Keywords : Pronunciation, minimal pairs.